Manfaat Berpikir Positif terhadap Pengembangan Kinerja Otak - Khoiriah Barokah (Jurnal Spiritual Healing, 2021)
Positive thinking is a way or way for an individual to know and obtain the meaning of life in an individual. Positive thinking is the beginning of what behavioral actions must be done. The way the brain works is to respond and coordinate the thoughts that enter the brain. This writing method is reference analysis. The results of writing are that the benefits obtained are so extraordinary due to the planting of positive thinking in the work system and brain memory. Thus, the structure, function and work of the brain can change, develop and not remain permanent, even with positive thinking can sharpen the level of creativity of brain function, so that humans can obtain intelligence and mental health, a stable physical will be found meaning and purpose of life.